Handel zagraniczny warzywami i ich przetworami w Polsce i w UE w latach 2002–2008 - Filipiak, Tadeusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
Foreign trade pays an important role in the development of both world and Polish economy. In the years 2002–2008 Poland reported negative balance of foreign trade of all kinds of products, while since 2003 the balance of trade with agricultural products was positive. In the structure of Polish export of agricultural products in the year 2008, fruits and vegetables paid a dominant role (ca. 20% of total export). In the years 2002–2008 the European Union was the net importer of all kinds of vegetables and vegetable products. Since the year 2004 when 10 New Member States accessed to the UE, the enlarged Community was the net importer of fresh tomatos, onions, peppers, courgettes, legumes and sweet corn. As the processed vegetables are concerned the EU net imported frozen vegetables, canned and dry tomatos. The positive trade balance was reported for canned vegetables and tomato puree. As the trade between Poland and other Member States is concerned, Poland reports positive balance of both fresh and processed vegetables. In the years 2002–2008 in Poland dominated positive and growing foreign trade balance with fresh vegetables and their products. It was possible thanks to positive foreign trade balance of processed vegetables, because the balance of trade with fresh vegetables was negative. Main exporting countries of Polish vegetables and their products were Holland, Germany and United Kingdom. Poland imported such products mostly from the UE, especially from Spain and Holland.